O MERCÚRIO EM PRAIAS CULTIVADAS DA BACIA DO JURUÁ NO ESTADO DO ACRE - Costa, M. L.; Rego, J. A. R.; Brabo, E. S.; Santos, O. C.; Jesus, I. M.; Almeida, H. D. F.; Martins, M. M. M. (Geochimica Brasiliensis, 2012)